Mechanisms of vesicular stomatitis virus inactivation by protoporphyrin ix, zinc- protoporphyrin ix, and mesoporphyrin ix - Oliveira, Christine Cruz (2018)
© 2017 American Society for Microbiology. All Rights Reserved.